Benthic Macroinvertebrates as Indicators of Water Quality in Asejire Reservoir, Southwest Nigeria - Asibor, Godwin I.; Adeniyi, Israel F. (International Journal of Scientific Research in Biological Sciences, 2022)
The water quality assessment of Asejire reservoir was carried out using benthic macroinvertebrates. Ten sampling stations were selected based on the reaches, vegetation pattern and impact of human activities on the reservoir using a Van Veen grab sampler. Collection and identifications was done using standard identification keys. Physicochemical parameters were determined using standard methods. The mean range of physicochemical parameters studied were; electrical conductivity 108±4.01µS/cm, pH 7.78±0.26, water temperature 26.19±0.38 0C, water transparency 1.46±0.13mg/L, TDS 85.0±4.32mg/L), turbidity 11.2±0.45 NTU, dissolved oxygen 4.57±0.27mg/L, biological oxygen demand 0.77±0.29 mg/L, with low values for phosphate, nitrate, sulpgate and chloride. There was no significant difference between the sampling sites in physicochemical parameters (p<0.05). Thirty-six (36) species belonging to Class Insecta, Arachnida, Malacostraca, Gastropoda, Bivalvia, Hirudinea and Gordiodea were identified and accounted for 8545 individuals. Increasing dominance of benthic macroinvertebrates followed: Insecta (50%), Gastropoda (27.8%), Bivalvia (8.3%), Malacostraca (5.6%), Arachnida (2.8%), Hirudinea (2.8%) and Gordiodea (2.8%). Correlation analysis between physicochemical parameters and macroinvertebrates showed a strong positive relationship (P<0.05). Presence of pollution intolerant species in most of the stations and accounting for more than 20% of the recorded individuals indicates a near-pristine ecosystem. However, the presence of pollution tolerant macroinvertebrates notably Chironomus sp. and Hirudo sp. in the Reservoir is a cause of concern and this indicate that the reservoir may not be totally free from pollution and therefore there is the need to have a robust monitoring plan in place to control anthropogenic pollutants and put measures in place to halt the introduction of more pollutant tolerant species into the Reservoir.